2013
DOI: 10.1186/1746-1596-8-70
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of 17-DMAG and TNF on cells through a mechanism related to the NF-kappaB pathway

Abstract: ObjectiveThe tumor necrosis factor (TNF) and the cellular NF-κB pathway protein IKKβ play important roles in various cellular processes such as cell proliferation, survival, differentiation, and apoptosis. A heat shock protein 90 inhibitor, 17-DMAG, can induce apoptosis of some tumor cells. This study is to determine the combined effects of 17-DMAG and TNF on malignant cells and the related mechanisms.MethodsWe have determined effects of 17-DMAG, an Hsp90 inhibitor, and TNF treatments on the small cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our study demonstrated that AG attenuated NF-κB activity and induced a synergistic increase in apoptosis in A549 cells treated with TNFα. In accord with past reports, the inhibition of NF-κB activation led to increased TNFα-induced apoptosis [ 57 ]. Moreover, AG reduced TNFα-stimulated IκBα degradation, which suppressed the nuclear translocation of NF-κB.…”
Section: Discussionsupporting
confidence: 92%
“…Our study demonstrated that AG attenuated NF-κB activity and induced a synergistic increase in apoptosis in A549 cells treated with TNFα. In accord with past reports, the inhibition of NF-κB activation led to increased TNFα-induced apoptosis [ 57 ]. Moreover, AG reduced TNFα-stimulated IκBα degradation, which suppressed the nuclear translocation of NF-κB.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have showed that encapsulating drugs to PLGA-PEG reduces dosage of drug and causes low adverse side effects of the drug (Mirakabad et al, 2013). 17DMAG is a hydrophilic gaeldamaycin derivative that can good bioavailability and better activity in vitro and in vivo and has significant anticancer activity (Sharp and Workman, 2006;Qu et al, 2013;Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PLGA-PEG (poly (DL-lactic-co-glycolic acid)-polyethyleneglycol)-17DMAG is a kind of nanoparticle that may be to inhibit the expression of HSP90 gene in lung cancer cell line (Pearl and Toft, 2008;Banerji, 2009;Qu et al, 2013;Sun et al, 2013). In this study, we investigated whether nanocapsulating 17DMAG improve the anti cancer effect of free 17DMAG in the A549 lung cancer cell line.…”
Section: Introductionmentioning
confidence: 99%
“…As a potent proteasome inhibitor, PS-341 inhibits various types of cancer, interestingly, Hsp90 inhibitor 17-AAG enhances PS-341-induced lung cancer cell death by degrading upstream regulators of IκB, IRAK-1, and IκB kinases (IKKs) (83). In addition, combination of 17-DMAG and TnF brings about synergistic killing of lung cancer cells via downregulation of IKKβ (84). Hsp90 inhibitor ganetespib induces loss of EMl4-AlK expression and depletion of multiple oncogenic signaling proteins in AlK-driven nSClC cells (85).…”
Section: Influence Of Hsp90 On Cell Cycle Regulation and Cell Apoptosismentioning
confidence: 99%